Evaluating Adherence to COVID-19 Quarantine Protocols at Two International Ground Crossings in Savannakhet Province, Lao PDR - Xaylovong, Khamsamay; Adjei-Gyamfi, Silas; Pongvongsa, Tiengkham; Moji, Kazuhiko; Aiga, Hirotsugu (BMC, 2026)
BACKGROUND: Border surveillance measures, including health screening and mandatory quarantine for travelers, are critical components of global pandemic response strategies. In Lao PDR, however, no known study has assessed the performance of the quarantine system, which was designed to protect the health of both citizens and incoming travelers, particularly during the COVID-19 pandemic and in preparation for future outbreaks. This study therefore evaluates adherence to the national COVID-19 quarantine protocols at two ground crossings (Vietnam-Laos and Thailand-Laos) in Savannakhet Province during the COVID-19 pandemic. METHODS: A retrospective cross-sectional study was conducted among 380 registered adult incoming travelers who entered Lao PDR via Dansavanh-Lao Bao border or Second Thai-Lao Friendship Bridge between April 2020 and March 2021. Data were extracted from point-of-entry registers, provincial hospital records, and quarantine facility registers. Overall quarantine performance (OQP) was defined as completion of the Lao PDR national quarantine protocol. Binary logistic regression was employed to identify the factors associated with OQP completion. RESULTS: Of the 380 incoming travelers, 277 (72.9%; 95%CI 68.2-77.1) completed the full quarantine procedures. Body temperature screening was conducted for 348 individuals (91.6%), with 13 (3.7%) presenting with fever ≥ 37.5 °C and referred for further screening. Among 335 incoming travelers directed to quarantine facilities, 264 (78.8%) completed the 14-day quarantine. Multivariate analysis revealed that female incoming travelers were significantly more likely to complete quarantine procedure than males (aOR: 1.84; 95%CI 1.14-2.96; p = 0.013). Those who traveled into the provinces other than Savannakhet had higher odds of quarantine completion (aOR: 1.78; 95%CI 1.49-3.26; p = 0.042). CONCLUSION: Based on locally defined indicators, the quarantine system achieved OQP rate of 72.9% which reflects an acceptable level of compliance. Gender and destination province were significant predictors of adherence. Enhancing communication strategies and standardizing strict quarantine procedures could improve border surveillance and preparedness for future public health emergencies.
Keywords: Border crossing; COVID-19; Ground crossing; Lao PDR; Pandemic preparedness; Quarantine; Surveillance; 4206 Public Health; 42 Health Sciences; Coronaviruses; Coronaviruses Disparities and At-Risk Populations; 3 Good Health and Well Being; 1103 Clinical Sciences; 1108 Medical Microbiology; 1117 Public Health and Health Services; 3202 Clinical sciences; 4206 Public health